The Delimitation of Greece’s Maritime Zones: Background, Recent Developments & Future Challenges in the Context of the Greek-Turkish Conflict - Koukakis, Georgios (HAPSc Policy Briefs Series, 2025)
On 16 April 2025 Greece published its Maritime Spatial Planning which inter alia depicted the limits of all of its maritime zones creating tension in the Greek-Turkish relations, as the delimitation of the maritime zones in the Aegean is the main reason behind the Greek-Turkish conflict. The purpose of this article is to present the current status of the Greek maritime zones in the context of the ongoing Greek-Turkish conflict, and how this dispute affects the national security of Greece and regional security in the Eastern Mediterranean.